Creative Learning: A Gateway to Professional Development - Pandey, Shiv Ram (Studies in ELT and Applied Linguistics, 2021)
This article presents insights on creative learning. It briefly describes the types of creative learning and ways to learning creatively. It discusses the usefulness of creative learning and ends with highlighting the need for creative learning on the part of children, students, teachers and the other individuals. It is truly an enabling, encouraging, engaging and inspiring activity on the part of learners. Creativity cultivates crucial capacity and commitment to learn and earn more conducive knowledge, skills and attitudes.